Module 1-8: Climate Smart Agriculture Investment Plan (CSAIP) Training Modules - Bioversity International and International Center for Tropical Agriculture; Ministry of Agriculture and Livestock Development, Kenya; Kenya Climate Smart Agriculture Multistakeholder Platform (2023)
This is the first module of an eight-module training series designed to equip national and subnational stakeholders with the skills and knowledge to tailor the Kenya Climate Smart Agriculture Investment Plan to different contexts with the goal of leveraging financial opportunities from diverse sources, such as the private sector actors, public institutions, international donors, and other important stakeholders who share the common goal of catalyzing transformative change in the agriculture sector.